2020
DOI: 10.18203/2394-6040.ijcmph20202987
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding mother-to-child transmission of HIV, its prevention, and associated factors among antenatal women attending a health care facility in district Srinagar, North India: a cross sectional study

Abstract: Background: HIV pandemic still remains an issue of major concern on a global scale with more than 37.9 million people estimated to be living with HIV in 2019 globally -an increase from 36.7 million in 2015. India has the third largest HIV epidemic in the world, with 2.1 million people living with HIV, with higher prevalence among men (0.25%) than women (0.19%) out of which children (15 years) accounts for 6.54%, while two fifth (40.5%) of total HIV infections are among females.Methods: A cross-sectional hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…It is more similar to a study conducted in Mekelle-Ethiopia, Katsina State-Nigeria, and South-Ethiopia. 30–32 This finding was slightly lower than studies conducted in Ambo-Ethiopia (93.6%), Hawassa-Ethiopia (97.4%), Srinagar District-North India (96.4%), and Hawassa-Ethiopia (93.3%) 15 , 37–39 but much higher than compared to a study done in Southwestern Nigeria (28.73%), Juba Teaching Hospital, South Sudan (51%). 36 This might be explained due to the difference in the geographical area, study period, and sample size.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It is more similar to a study conducted in Mekelle-Ethiopia, Katsina State-Nigeria, and South-Ethiopia. 30–32 This finding was slightly lower than studies conducted in Ambo-Ethiopia (93.6%), Hawassa-Ethiopia (97.4%), Srinagar District-North India (96.4%), and Hawassa-Ethiopia (93.3%) 15 , 37–39 but much higher than compared to a study done in Southwestern Nigeria (28.73%), Juba Teaching Hospital, South Sudan (51%). 36 This might be explained due to the difference in the geographical area, study period, and sample size.…”
Section: Discussioncontrasting
confidence: 55%
“… 15 , 38–40 Yet, it was much different from the study done in Abidjan-Côte d’Ivoire, Benue-Nigeria, Juba-South Sudan, Srinagar District-North India (91.4%), and Bobo-Dioulasso Burkina Faso (58.4%, 55.7%, 78.4%, 91.5%, and 81.8% respectively). 36 , 37 , 41 , 42 This could be due to the difference between this and the later studies, in that as awareness and knowledge increase; the habit of HIV/AIDS testing also increases.…”
Section: Discussionmentioning
confidence: 86%
“…Maternal knowledge about MTCT of HIV/AIDS and its prevention is a cornerstone for elimination of MTCT of HIV. Although the majority of the population in SSA are lived in rural areas with restricted availability and accessibility of health facilities, most of the studies on knowledge about MTCT of HIV/AIDS and its prevention were conducted among available women, such as those who came to the health facility for their antenatal care follow up [20][21][22][23][24]. In addition, up to our knowledge, there is no updated information on this regard using nationally representative data (using the recent DHS surveys) at the SSA scale.…”
Section: Introductionmentioning
confidence: 99%
“…However, the attitude-related findings of this study were very similar to the attituderelated findings of an Indian study by Mukhtar et al which reported that 96.4% agreed to be counselled and tested for HIV, 77.3% agreed to the importance of HIV testing in husbands, 90.2% agreed to the effectiveness of PMTCT in reducing the HIV transmission risk of a baby and 12.5% agreed to the importance of feeding choice of HIV-positive mothers for their infants. 16 This study showed that 85.5% of the study pregnancies were tested for HIV through the procedures of PMTCT. This practice proportion was slightly lower when compared with the practice proportion (91.5%) resulting from a recent similar Indian study.…”
Section: Associated Factorsmentioning
confidence: 90%
“…These findings were comparable with a recent crosssectional Indian study on 366 pregnant women. 16 Nonetheless, providing more information about the nature of the PMTCT and associated activities should be enforced to promote a better understanding of pregnant women concerning preventive measures for HIV/ALDS.…”
Section: Associated Factorsmentioning
confidence: 99%